Case study of promoting Chinese calligraphy through infomercial mini documentary in Universiti Malaysia Kelantan. - Lee Soon Zi, Sally (2015)
Cultural heritage has an important role in civilization of a nation.This cultural heritage must be preserved because it has its own identity.Chinese calligraphy is a unique gem of Oriental culture.It is comparable to painting in its ability to express emotion through a rich variety of form and design.This research was conducted with the objective of developing Chinese calligraphy tradition in a new form of documentation which is mini documentary in order to improve the level of understanding and further the public interest to preserve and inherit the tradition of Chinese calligraphy.This is due to the extinction of the traditional heritage in this modernization.A study was conducted to identify the level of understanding of students in University Malaysia Kelantan to traditional Chinese calligraphy.A number of methods is undergone to collect data such as interviews,questionnaires,literature review and research of electrical and electronic sources.The findings have found that most of the students do not know and less interest in this tradition.Thus,this research will discuss about the tradition of Chinese calligraphy and the level of understanding of students from University Malaysia Kelantan about this cultural traditions.Therefore,solutions can be made in sustaining this valuable tradition,particularly among students at the University Malaysia Kelantan.